Nodular fasciitis of the vulva: a challenging histopathologic diagnosis supported by the detection of USP6 gene rearrangement. Issue 6 (18th March 2016) - Pichler Sekulic, Simona; Sekulic, Miroslav
Abstract : Nodular fasciitis involving the vulva on physical examination can mimic a Bartholin gland lesion, and histologically can have overlapping features with more ominous mesenchymal pathologies. We describe a case in which a 52‐year‐old perimenopausal woman presents with a vulvar mass. After an initial biopsy and later excision, the myofibroblastic lesion was noted to have areas of differing cellularity, with compact nodule formations at the periphery. Immunohistochemical staining showed lesional cells to be positive for desmin, estrogen receptor, progesterone receptor, and smooth muscle actin, and negative for CD34, ALK‐1, myogenin, caldesmon, S100, and wide spectrum (Oscar) cytokeratin. Desmin is generally negative in this lesion type, but the positivity in this case was considered to be secondary to the origin of the myofibroblastic cells of the vulva. The morphologic pattern and immunophenotype favored a diagnosis of nodular fasciitis, however, the degree of hypercellularity and desmin positivity warranted further analysis. The diagnosis was supported with fluorescence in situ hybridization that demonstrated USP6 gene rearrangement. This highlights the necessity in certain challenging cases for ancillary molecular and/or cytogenetic analysis.